The Effect of Online Micro Teaching-Learning on The Perception of Managing IRE Students' Class - Helma Deti; Wedra Aprison; Risdoyok Risdoyok (Nazhruna: Jurnal Pendidikan Islam, 2022)
This article is motivated by a regulation from the government that orders the teaching and learning process to be carried out online or online. This article aims to find out the description of online micro teaching-learning, perceptions of managing classes, and the effect of online micro teaching-learning on perceptions of managing classes for Islamic religious education students in semester 6 of the 2020/2021 academic year at IAIN Bukittinggi. This research uses a correlational type of quantitative approach. Sampling used a simple random sampling technique by taking 20% of the population of 174 students, so the sample of this study amounted to 35 students and the data collection technique used a questionnaire which was distributed via a google form. The research results of online learning micro-teaching for Islamic religious education students are in the high category with a percentage of 46%, the perception of managing the class of Islamic religious education students lies in the medium category with a percentage of 48.5 % while the effect of online micro teaching-learning on the perception of managing the class is 0.470 and the results of the determination test obtained a value of 22.10%. So, the perception of managing a student's class is 22.10% influenced by online micro teaching-learning while the remaining 77.90% is influenced by other factors.